Il concetto di ordine pubblico: uno sguardo retrospettivo dai lavori preparatori dell’Assemblea Costituente (Stato, Chiese e pluralismo confessionale, 2025)
The concept of public order: a retrospective look at the preparatory work of the Constituent AssemblySince its initial formulation and application, the concept of public order has consistently proven difficult to define with precision. Over time, it has been interpreted through a variety of lenses: material, ideal, public, domestic, and international. This paper offers a retrospective analysis of how the concept was addressed during the constitutional debate. Specifically, it examines how public order was discussed in the reports submitted by members of the Constituent Assembly, the debates these reports generated within the various subcommittees, and, ultimately, the deliberations held during the plenary session. The aim is to clarify the origins of the concept within the Italian constitutional context, in order to provide a clearer understanding of its key aspects in the contemporary legal framework.SOMMARIO: 1. Il concetto di ordine pubblico: un tentativo definitorio - 2. Il concetto di ordine pubblico: tra passato e presente 3. Le relazioni presentate presso le Sottocommissioni della Commissione per la Costituzione - 4. Il dibattito in seno alle Sottocommissioni della Commissione per la Costituzione - 5. Il dibattito in Assemblea Costituente - 6. Brevi conclusioni: un’eco dal passato.